Informational website : the development of culture-centered web design for the Bidayuh Bukar-Sadong community / Jasmine Felixson - Felixson, Jasmine (2018)
A culture-centered web design is a website where the culture is being the center of discussion in the website. Culture is something that need to be preserved and maintained. It reflects the characteristic of an ethnic. Culture does attracts visitors or tourist as it is unique. It is very important to learn and know about your own culture as it represents your own ethnic. Informational Website : The Development CultureCentered Web Design for the Bidayuh Bukar-Sadong Community is about developing a website which focuses on the Bidayuh BukarSadong Community culture. This project is developed by fulfilling three (3) main objectives which are to identify the requirement for Informational Culture-Centered Web Design for the Bidayuh BukarSadong Community, to design and to develop Informational Culture-Centered Web Design for the Bidayuh Bukar-Sadong Community. This website provide benefits to few parties such as tourists, the Bukar-Sadong community and the Sarawak Government. It brings benefit to the tourists as they will be able to get complete information of the culture and also experience the culture. As for the Bidayuh BukarSadong community, it will ease the process of preserving the culture and introducing the culture to the outsiders. Sarawak Government will also benefit economically when visitors or tourists come and invest in the country. User Centered Design (UCD) approach is used to examine the problem thoroughly and also to look for solutions. There are four (4) phases involved in the approach, which are research, define, develop and evaluate. User testing are conducted in order to determine whether the website meets user requirement or otherwise. Five (5) users are selected to complete tasks that were assigned to them in order to do user testing. Therefore, from the testing conducted, it is found that users are interested in enabling the 360 degree and 3D image feature where it allows users to interact and experience the culture virtually and emotionally .Lastly, there are still few enhancement needed to be done to the project. Enhancement such as developing it on mobile platform can be done for future work.